Scalable synthesis of 5,11-diethynylated indeno[1,2-b]fluorene-6,12-diones and exploration of their solid state packing - Bradley D. Rose; Peter J. Santa Maria; Aaron G. Fix; Chris L. Vonnegut; Lev N. Zakharov; Sean R. Parkin; Michael M. Haley (Beilstein Journal of Organic Chemistry, 2014)
We report a new synthetic route to 5,11-disubstituted indeno[1,2-b]fluorene-6,12-diones that is amenable to larger scale reactions, allowing for the preparation of gram amounts of material. With this new methodology, we explored the effects on crystal packing morphology for the indeno[1,2-b]fluorene-6,12-diones by varying the substituents on the silylethynyl groups.